STUDY ON THE CORRELATION BETWEEN SELF-ESTEEM, PHYSICAL CAPACITY OF EFFORT AND THE SOMATOMETRIC PARAMETERS - Trofin Petrut Florin; Abalasei Beatrice; Drosescu Paula; Cojocaru Dumitru (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2013)
Self-esteem is the result of the analogy between self-concept and self-image; the latter is formed by the self-perception of the physical, emotional, cognitive, social, etc characteristics. This paper treats the correlation between self-esteem and physical capacity from the perspective that each social actor communicates with the environment through the body and that the body represents the instrument of social image elaboration, thus facilitating self-knowledge and the knowledge of the others. It actually represents the reflection of the beliefs that have always made up the general opinion. The specialized literature ascribes to the body the role of "mediator" in the relationship with the self, with the environment and with the others. Within an interaction, the dialogue partners give much importance to the non-verbal language, which transmits information that will bring advantages or disadvantages to the result of the communication. Kinaesthesia has a fundamental role in the body language and that is why the investigative approach is oriented toward the identification of a reciprocity relationship between physical capacity and self-esteem (with all its components). In this sense, based on the research outcomes, we can talk about the elements influencing the well-being of the social actors, about the correlation between the level of physical performance and self-esteem, between the last variable and the somatometric indices, as an element providing information on self-perception. A high self-esteem favours the development of human potential.